Lost Waterways, Shifting Identities : Road Infrastructure and the Morphology of Coastal Village Settlements in Kuching - Azmah, Arzmi; Nana, Zheng (Universiti Malaya, 2025)
This paper focuses on how infrastructural planning and urban expansion of Kuching has impacted the growth, social fabric, and cultural identity of the riverine coastal villages in its vicinity. The villages we studied are Sejingkat, Buntal, Bako, and Muara Tebas. Each village's development was shaped by surrounding land-use activities, like factories, ports, educational institutions, or rainforest tourism. Through historical analysis, spatial mapping, and in-depth interviews with village chiefs, we explore the significance of waterways and embedded road networks in shaping the settlement patterns, and their subsequent growth trajectories. The results of our analysis highlight the intricate relationship between ongoing planning policies, socio-economic activities, infrastructure, and cultural identity in these coastal communities. We propose strategies for integrating local participation, existing cultural landscapes and values into future planning efforts, with the aim of preserving the identity of coastal village settlements while ensuring their sustainable development in Kuching. Ultimately, we call for a more holistic approach to road infrastructure development and sectoral planning, to minimize negative impacts for the local communities.